The prevalence of traditional bullying and cyber-bullying among university students - Saloojee, Nasreen (My University, 2020)
Bullying has been widely recognised as a significant concern among primary and high schools as well as within the workplace setting. These settings have time and again been at the forefront of research. However, not much is known about the prevalence of bullying within the tertiary education setting. This research study explored the prevalence of traditional bullying and cyber-bullying among South African University students. This study also sought to investigate the role demographic factors play when university students experience traditional bullying or cyber-bullying in addition to the question of whether students who experience either form of bullying regard it as a form of trauma. A quantitative approach was used to carry out this study. The sample consisted of young adults between the ages of 18 and 23 years old (n = 148) and was non-representative. This study made use of a demographic questionnaire, the Revised Olweus Bully/Victim Questionnaire, the Cyber Bullying Behaviours and Victimization Experiences Measure, as well as the Impact of Event Scale-Revised, in order to attain data. The statistical analyses were carried out through the use of descriptive statistics, frequencies, cross-tabulations and Pearson’s chi-square and correlation tests were carried out. The current study’s overall results indicate that the prevalence of traditional bullying among university students is 25.8%, with 21.6% being verbally bullied, 32.5% experienced being socially excluded, and 19.8% experienced social bullying. In terms of being cyber-bullied, 31.1% of students admitted being afraid to go online, and 33.1% of students reported having had a social media post or message shared online about them which they did not want other people to see. In comparison, a total of 33.8% of students admitted to purposefully sending aggravating or humiliating text messages or instant messages from their cellphone to another individual. In terms of the demographic factors; gender, race, and age, were all not statistically significant in terms of the prevalence of traditional bullying and cyber-bullying. Furthermore, cyber-bullying and being a victim of traditional bullying were found statistically significant to post-traumatic symptoms
A research project submitted in partial fulfilment of the requirements for the degree of Masters of Education Psychology to the Faculty of Humanities, University of Witwatersrand, 2020
Keywords: Cyberbullying--South Africa; College students--South Africa